2022
DOI: 10.6007/ijarbss/v12-i7/13974
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Suicide and Youth: Biological, Psychological, Social and Environmental Risk Factors

Abstract: Introduction: Suicide affects the lives of many individuals all over the world and is a severe public health concern. Among all the ages, youth suicide is one of the severe topics to be concerned about due to the years of their life lost. As a result, we require a thorough understanding of the risk factors contributing to young suicide cases. This systematic review uses thematic analysis to identify common themes and topics in recent literature on suicide and youth: biological, psychological, social, and envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Environmental factors including stressful life events preceded suicidal attempts (Ching et al ., 2022). These may not directly cause suicide, but they contribute to underlying psychological difficulties that make teenagers more vulnerable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Environmental factors including stressful life events preceded suicidal attempts (Ching et al ., 2022). These may not directly cause suicide, but they contribute to underlying psychological difficulties that make teenagers more vulnerable.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 1 According to the Centers for Disease Control and Prevention, it is the second leading cause of death among young people aged 15 to 24 in the United States. 2 Approximately 80% of all suicides occur in low and middle-income countries, with Eastern and Central European countries having the highest suicide mortality rate. 1 Multiple studies have indicated a significant increase in suicide attempts among teenagers in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…These changes make adolescents vulnerable to mental health issues, high-risk behaviors, suicidal ideation, and suicidal behavior. 6 Several factors have been identified as potential influences on suicidal attempts during adolescence, including previous suicide history, 1 , 7 , 8 psychiatric disorders, 1 , 2 , 9 , 10 and substance abuse disorders. 2 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, a wide range of globally published articles has discussed and evident that negative life events can impact a child in various ways. For example, causing behavioral problems, poor academic performance, poor health outcomes, early death, violence perpetration, sleep problem, and premature mortality (Blum et al, 2019;Blodgett & Lanigan, 2018;Brown et al, 2009;Park et al, 2020;Petruccelli et al, 2019;Ray et al, 2021;Khairi et al, 2022;Bahrami et al, 2021;Ching et al, 2022). Concerning the mental health of the child due to exposure to ACEs and symptoms of depression among Malaysian single-parent adolescents are limited.…”
Section: Introductionmentioning
confidence: 99%